Computer simulation of the system of condensate purification plant of NPP with WWER-1000 reactor - Медведєв, Ромуальд Броніслівович; Сангінова, Ольга Вікторівна; Мердух, Світлана Леонідівна (Eastern-European Journal of Enterprise Technologies, 2012)
This article represents modeling and analysis of the system of condensate purification plant using the simulation methods